Mapping the Landscape of Organizational Branding: A BERTopic-Driven Exploration - Kiliç, Tamer; Özsaçmaci, Bülent (International Review of Management and Marketing, 2026)
This study employs a comprehensive, two-stage methodology, systematic data retrieval from the Scopus database followed by a Bidirectional Encoder Representations from Transformers (BERTopic)-driven text analysis, to map the thematic landscape of 7,920 articles on organizational branding. The analysis uncovers fifteen predominant topics that together portray an increasingly granular field. Salient streams encompass employer branding and talent attraction, consumer brand loyalty, organizational identity and corporate heritage, place and destination branding, and emerging technology- enabled trust mechanisms such as blockchain. Time-series results confirm an accelerating expansion of branding scholarship after 2000, underscoring the shift from product-centric tactics toward organization-wide brand strategies that intertwine corporate purpose, stakeholder engagement, and sociotechnical change. These findings reinforce branding’s role as both a strategic asset and a sociocultural practice, informing theory development in legitimacy, stakeholder co-creation, and the dynamic interplay between technology and organizational identity. The study concludes that an integrative perspective, combining large-scale computational analysis with deep qualitative interpretation, remains essential for capturing the full complexity of organizational branding in a rapidly evolving social landscape.